Case Report: Omadacycline in the treatment of macrolide-unresponsive Mycoplasma pneumoniae pneumonia in an adolescent patient - Xu, Limin; Fang, Changquan (Frontiers in Cellular and Infection Microbiology, 2023)
Omadacycline is a novel tetracycline antibiotic that exhibits good in vitro antibacterial activity against atypical pathogens such as Mycoplasma pneumoniae. It is approved for the treatment of adults with community-acquired bacterial pneumonia. However, the safety and efficacy of omadacycline in pediatric patients under 18 years of age have not yet been established. In the present paper, we report a case of pediatric community-acquired pneumonia in which initial empirical anti-infective therapy had failed. The patient received empirical anti-infective therapy with azithromycin and other antimicrobial agents upon admission but showed a poor clinical response and developed secondary tinnitus and liver dysfunction. After the confirmation of M. pneumoniae infection through metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid, an antibiotic switch to omadacycline was made. Thereafter, the patient's condition improved, and no adverse reactions were observed. These findings demonstrate that mNGS enables the identification of infection-causing pathogens in patients with unresponsive pneumonia. Omadacycline can be considered as an alternative option for anti-infective therapy in pediatric M. pneumoniae pneumonia, especially when the presence of bacterial resistance, adverse drug reactions, or organ failure are taken into consideration.